A healthy peer status: Peer preference, not popularity, predicts lower systemic inflammation in adolescence. (November 2019) - de Bruine, Marieke; Giletta, Matteo; Denissen, Jaap J.A.; Sijtsema, Jelle J.; Oldehinkel, Albertine J.
Highlights: Independent roles of peer preference and popularity on adolescents' inflammation. Peer preference at age 13 was associated with lower levels of hsCRP at age 16. Positive effect of peer popularity on hsCRP depended on early adversity exposure. The effect of peer preference on hsCRP was not exacerbated by early adversity. Abstract: In adolescence, sensitivity to peers is heightened, which makes peer experiences highly salient. Recent work suggests that these experiences may influence individuals' immune system functioning. Although there is a need to investigate which types of developmental salient social experiences affect inflammation, no studies have examined the role of peer status in inflammatory activity so far. This study is the first to examine the unique role of different types of peer status (i.e., peer preference and peer popularity) on systemic inflammation in adolescence, and the extent to which this association is moderated by early childhood adversity. Participants were 587 Dutch adolescents from the TRacking Adolescents´ Individual Lives Survey (TRAILS). Data were collected when participants were 11 ( SD  = .56), 13 ( SD  = .53) and 16 ( SD  = .71) years old, respectively. At age 11, early childhood adversity (e.g., hospitalization, death within the family) between 0–5 years was assessed via parent interviews. At age 13, peer preference and peer popularity were assessed with peer nominations of classmates. At age 16, high sensitive C-reactive protein (hsCRP), a marker of low-grade systemic inflammation, was assessed with a venipuncture blood draw. Results showed that adolescents who were rated low on peer preference at age 13 exhibited higher levels of hsCRP at age 16. Importantly, these effects remained after controlling for several covariates, including age, sex, peer victimization, smoking behavior, SES, fat percentage, physical activity and temperament. Additionally, we found a positive effect of peer popularity on hsCRP that depended on early childhood adversity exposure. This suggests that for those adolescents who experienced little early childhood adversity, high levels of peer popularity were associated with high levels of hsCRP. Overall, these findings suggest that it is important to take into account the independent roles of peer preference and peer popularity, as specific types of peer status, to better understand adolescent systemic inflammation.